Optimasi perancangan turbin air axial aliran horisontal menggunakan analysis of variance - Nurdin, A.; Himawanto, D.A.; Hadi, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
The number of blades factor and the blade angle factor on the propeller turbine will be affect to the performance, and one of these factors is dominant affected for the turbine performance. To optimize the design of propeller turbines, must be known the factors that most influence its performance. This study aims to investigate the significance test of difference value in shaft power due to the number of blade factor and the blade angle factor, and to determine the most dominant influence of these factors. Hypothesis test method of these factors on this study using analysis-of-variance or ANOVA with SPSS 17.0 software. The results of this study indicate the significant test in shaft power value in the number of blades factor and the blade angle factor, and there is a relationship between both factors influences in shaft power value significantly. This study also shows the blade angle factor has the most dominant effect in shaft power value, beside the number of blade factor.